Photon-tagged measurements of jet quenching with ATLAS - Onofre, A. (2019)
Events containing a high transverse momentum (pT) prompt photon offer a useful way to study the dynamics of the hot, dense medium produced in heavy ion collisions. Because photons do not carry color charge, they are unaffected by the medium, and thus provide information about the momentum, direction, and flavor (quark or gluon) of the asso- ciated hard-scattered parton before it begins to shower and become quenched. In particular, the presence of a high-pT photon can be used to select pp and Pb+Pb events with the same configuration before quenching, limiting the effects of quenching-induced selection biases present in other jet measurements. The large statistics pp and Pb+Pb data delivered by the LHC in 2015 allow for a detailed study of photon-tagged jet quenching effects, such as the overall parton energy loss and modified structure of the component of the shower which remains correlated with the initial parton direction (e.g. in cone). In this proceeding, photon-tagged measurements of jet quenching by ATLAS are reported.